Synthesis of sulfur doped g-C3N4 with enhanced photocatalytic activity in molten salt - Guan, Keke; Li, Junyi; Lei, Wen; Wang, Honghong; Tong, Zhaoming; Jia, Quanli; Zhang, Haijun; Zhang, Shaowei (Journal of Materiomics, 2021)
In this paper, sulfur doped g-C3N4 (S-g-C3N4) was successfully prepared at 500 °C for 3 h via a modified molten salt method using dicyandiamide as the main raw material, trithiocyanuric acid as the sulfur source and LiBrKCl as the reaction medium. The as-prepared SCN5.0% sample (the mass ratio of trithiocyanuric acid to dicyandiamide was 5.0%) composed of irregular flakes showed a band gap of 1.83 eV, which was narrower than that (2.55 eV) of pristine g-C3N4. The SCN5.0% sample also exhibited an outstanding absorption capacity of visible light. Moreover, the photodegradation rate toward methylene blue and tetracycline were respectively 10 and 20 times as high as that of bulk g-C3N4 prepared by conventional heating methods, confirming its superior photocatalytic performance. These results can be attributed to that the replacement of lattice nitrogen with sulfur atom tuned the electronic structure of g-C3N4, improved the absorption of visible light, optimized the separation of photogenerated electron-hole pairs, and consequently enhanced the photocatalytic activity of g-C3N4. Moreover, the trapping experiments implied that hole (h+) and superoxide radical (·O2−) were the main active species in the process of photodegradation. [Display omitted] •Sulfur doped g-C3N4 was successfully prepared via a facile molten salt method.•The S—CN5.0% had a narrower band gap (1.83 eV) compared to pristine g-C3N4 (2.55 eV).•The S—CN5.0% had a higher degradation rate of MB and TC compared to pristine g-C3N4.•The S—CN5.0% exhibited a higher normalized degradation rate than previously reported.